The Process of Acceptance among Rheumatoid Arthritis Patients in Switzerland: A Qualitative Study - Zlatina Kostova; Maria Caiata-Zufferey; Peter J Schulz (Pain Research and Management)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic, painful disease with many injurious psychological effects. Acceptance is an important component of pain management and is associated with improved quality of life, and lower levels of pain and depression. While studies have begun to identify the stages of acceptance, little is known about factors influencing the ease and speed with which patients pass through these stages.